Implementasi Sistem Kursi Roda Elektrik Berbasis Nodemcu Esp8266 Pada SLB Dinamika Bekasi - Muhammad Hannan; Ahmad Chusyairi (Jurnal Ilmiah Informatika, 2024)
The conventional wheelchair system at SLB Dinamika Bekasi serves to assist students in carrying out activities in the school environment. The use of wheelchairs at the school is still not optimal with several problems, such as the activities of children with disabilities at school require constant supervision and assistance to adapt to the surrounding environment, so schools need to create an environment that supports the development of students with disabilities, both academically and non-academically. In addition, there are accessibility limitations such as inclines and declines in the school environment that make it difficult for students to carry out their activities. By implementing an electric wheelchair system based on NodeMCU ESP8266, this research successfully creates a more efficient and convenient solution. This system allows control of the wheelchair via a smartphone using the MIT App Inventor application, which makes it easy for users to move the wheelchair forward, backward, right and left easily. The method used in this research is the prototype method which consists of several stages such as communication, quick plan, modeling quick design, construction of prototype and deployment delivery & feedback. The test results show that the system works well, and has great potential to be further developed at SLB Dinamika Bekasi.